PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PELANGGAN GRAB DI MALANG (STUDI PADA MAHASISWA KOS DI KELURAHAN TLOGOMAS MALANG) - Yogi Eko Purwanto; Agus Widarko; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract            The reasearch aims to find out about how the influence of price and service quality on loyalty with customer satisfaction is an intervening variable for grab customer in malang. And rather than that researchers use case studies on boarding students in the tlogomas malang village itself. Using a quantitative approach, and data obtained through survey method with questionnaire questionnaire instrument. Which is the population is the grab consumers of boarding school students in the sample if the subject is less than one hundred is better taken all so that the results of the analysis include test instrument (validity test, reliability test, normality test, path analysis), and hypothesis testing ( T test, sobel test).Kata Kunci: price, service quality, customer satisfaction layolty grab.